2018
DOI: 10.1177/1176934318768781
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Proteins Containing Amyloidogenic Regions in the Proteomes of Bacteria of the Order Rhizobiales

Abstract: Amyloids are protein fibrils with a highly ordered spatial structure called cross-β. To date, amyloids were shown to be implicated in a wide range of biological processes, both pathogenic and functional. In bacteria, functional amyloids are involved in forming biofilms, storing toxins, overcoming the surface tension, and other functions. Rhizobiales represent an economically important group of Alphaproteobacteria, various species of which are not only capable of fixing nitrogen in the symbiosis with leguminous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 92 publications
1
6
0
Order By: Relevance
“…Detergent-resistant fractions of R. leguminosarus were also found to contain other virulence proteins, like NodT, which is probably involved in the secretion of nodulation factors [94]. This corresponds to the previously obtained bioinformatic data, which demonstrated that amyloidogenic regions in proteins of species belonging to the order Rhizobiale tend to co-occur with membrane or extracellular proteins, many of which are associated with virulence of these bacteria [95]. Overall, it becomes apparent that amyloids play an important role in the virulence of bacteria by promoting their interaction with a multicellular host.…”
Section: Discussionsupporting
confidence: 68%
“…Detergent-resistant fractions of R. leguminosarus were also found to contain other virulence proteins, like NodT, which is probably involved in the secretion of nodulation factors [94]. This corresponds to the previously obtained bioinformatic data, which demonstrated that amyloidogenic regions in proteins of species belonging to the order Rhizobiale tend to co-occur with membrane or extracellular proteins, many of which are associated with virulence of these bacteria [95]. Overall, it becomes apparent that amyloids play an important role in the virulence of bacteria by promoting their interaction with a multicellular host.…”
Section: Discussionsupporting
confidence: 68%
“…Furthermore, the results of the LEfSe analysis in female and male 3xTg-AD mice at 3 and 5 months old in fecal samples, show bacteria with a statistically significant change in LDA scores such as Xanthomonadaceae , Oxalobacteraceae , Streptomycetaceae , Koribacteraceae , and Streptomycetaceae families, Gemella , Dehalobacterium , Clostridium , Allobaculum , Selenomonas , Veillonella , Lactococcus , Desulfovibrio , Bradyrhizobium , Campylobacter , Erythrobacter , Neisseria , Flexispira , Microbacterium , Collinsella , Atopobium , Pedobacter , and the S1 genera. These microorganisms have been associated with both pre-clinical models and patients who present AD mainly; however, other bacteria are related to aging, cognitive decline, cerebral damage, and inflammatory response in mice and humans ( Thomas et al, 2012 ; Wang et al, 2016 ; Bonfili et al, 2017 ; Harach et al, 2017 ; Morris et al, 2017 ; Vogt et al, 2017 ; Zhang et al, 2017 ; Aguayo et al, 2018 ; Alonso et al, 2018 ; Antonets et al, 2018 ; Bäuerl et al, 2018 ; Dong et al, 2018 ; Zhuang et al, 2018 ; Haran et al, 2019 ; Li et al, 2019 ; Zhan et al, 2019 ; Beydoun et al, 2020 ; Na et al, 2020 ; Westfall et al, 2020 ). These results suggest that bacteria families and genera are representative microorganisms of gut microbiota of disease that could be considered a useful tool for diagnostic as well as a progression biomarker of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Every year, more and more data are accumulated on the amyloidogenic properties of proteins with a β-barrel structure predicted as their native one. Moreover, while for some of them the ability to form amyloid fibrils is currently predicted by proteomic screenings [ 221 ] or in silico methods [ 222 , 223 ], for others, experimental confirmation of the formation of bona fide amyloids on their basis has already been obtained in vitro and, more rarely, in vivo. Functional amyloids formed by β-barrel proteins in vivo have recently been identified in eukaryotes (plants) [ 18 ] and prokaryotes (bacteria) [ 62 , 63 , 64 ], where they are involved in nutrient storage and, probably, supra-organismal interactions.…”
Section: The Transition Of β-Barrel Proteins To Amyloidsmentioning
confidence: 99%